Extrusion processing of feedlot diets - Depenbusch, Brandon E. (Kansas State University, 2010)
A series of studies were conducted to evaluate extrusion processing of finishing diets on growth performance, carcass characteristics, and meat quality attributes of feedlot cattle. Extruded diets were processed in a 24:1 (length/diameter) corotating, fully intermeshing twinscrew extruder (model BCTG-62, Bühler AG CH-9240, Uzwil, Switzerland). In Experiment 1, extrusion processing of corn based diets decreased dry matter intake (DMI) and improved gain efficiency (G:F) by 15% compared to heifers fed steam-flaked corn (SFC) diets. Carcass characteristics were not different between treatments. Steaks from heifers fed SFC diets were juicier and had a less pronounced off-flavor than steaks from heifers fed extruded diets. In Experiment 2, average daily gain (ADG), DMI, G:F, carcass characteristics, and meat quality attributes were not different between heifers fed SFC and extruded processed corn diets. In Experiment 3, we evaluated different degrees of extrusion processing by altering the level of process water added to the extruder. Mechanical energy inputs, die pressure, die temperature, and torque of drive motor decreased as the level of water added to the extruder increased from 4% to 12%. Water addition did not affect DMI or ADG of feedlot heifers. However, live body weight (BW) and G:F decreased as the level of process water increased. Gain efficiency (carcass-adjusted basis) was 3% greater for extruded corn diets processed with 4% water compared with SFC diets and was 6% poorer than SFC diets when processed with 12% water. Apparent total tract digestibility was not different, but IVDMD improved with increasing levels of water. Improvements in G:F when fed extruded feed was variable among the 3 studies. This may be due, in part to severe infestation by European Starlings during Experiment 1. Impact of feed depredation by starlings was therefore evaluated. Starlings consumed 86% of the SFC diet offered to them compared to, none of the extruded corn diets. In addition, starlings preferentially selected for the energy dense portion of the rations (steam-flaked corn). Therefore, it is plausible that a portion of the 15% improvement in G:F observed in Experiment 1 for heifers fed extruded corn diets can be attributed to differences in feed depredation by starlings. Finally, two studies were conducted to evaluate extrusion processing of sorghum-based diets. In the first experiment, DMI was greater and G:F was poorer for heifers fed extruded sorghum diets compared to heifers fed steam-flaked sorghum (SFS) diets. However, carcass characteristics and meat quality attributes were not different. In the second study, particle size of the ground sorghum added to the extruder was evaluated. Processing sorghum to a smaller particle size (581 μm) prior to extrusion processing decreased DMI, improved G:F, and increased apparent total tract digestibility compared with larger particle sizes (1,264 μm). However, heifers fed SFS diets were still more efficient that heifers fed extruded diets made with either particle size of sorghum. Overall, this research suggests that extruding complete diets into homogeneous pellets may improve G:F of cattle fed corn-based diets while reducing feed depredation of starlings. It is also clear from our results that G:F is improved to a greater extent to processing diets under high shear conditions (i.e., high mechanical energy inputs) than when processed under low shear conditions.
Keywords: Extrusion; Meat; Feedlot; Roughage; Growth; Grain; Agriculture, Animal Culture and Nutrition (0475)